MENINGKATKAN HASIL BELAJAR MATERI BANGUN DATAR MENGGUNAKAN MEDIA TANGRAM SISWA KELAS IV C SD NEGERI 015 TANJUNGPINANG TIMUR TAHUN PELAJARAN 2022/2023 - Saripuddin; Mega Riyawati; Hambriyadi (STAI Miftahul Ulum Tanjungpinang, 2024)
The problem addressed in this research is students' difficulty in learning plane geometry in mathematics. The objective is to enhance students' learning outcomes using the tangram media in class IV C. This study adopts the Classroom Action Research (CAR) method, conducted over two cycles, each comprising planning, action implementation, observation, and reflection stages. The research subjects are the students of class IV C at SD Negeri 015 Tanjungpinang Timur, with a sample size of 32 students. Data collection techniques involve observation, tests, interviews, questionnaires, and documentation, analyzed through both qualitative and quantitative approaches. The results reveal that the use of tangram media for plane geometry in mathematics is successfully implemented. The mathematics KKM (Minimum Mastery Criteria) is set at 75, with a classical learning completeness threshold of 70%. The percentage of student completeness in the pre-cycle shows 11 students passing (34.3%) with an average score of 65.46. In the first cycle, there is an increase with 14 passing students (43.1%) and an average score of 71.56. The second cycle demonstrates further improvement with an average score of 76.87, and 27 passing students (84.3%). Consequently, there is an enhancement in the learning outcomes of class IV C students at SD Negeri 015 Tanjungpinang Timur through the utilization of tangram media in the subject of plane geometry in mathematics.